KINERJA KEUANGAN PT TELKOM INDONESIA (PERSERO) TBK SAAT PANDEMI COVID -19 - Faradina Inda Wardhani (Jurnal Ekonomi STIEP, 2021)
Financial performance is a description of the company's financial condition which is analyzed by means of financial analysis, which can reflect the company's work performance. This study aims to determine and compare the financial performance conditions of PT Telkom Idonesia (Persero)Tbk before and during the COVID-19 pandemic. The method of analysis used in this research is descriptive method whose purpose is to analyze any data that has been processed and then draw conclusions. This type of research is descriptive qualitative. The results showed that the financial performance had increased in 2020.